2010
DOI: 10.1007/s00405-010-1420-y
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal effects of nasal allergen provocation in singers with allergic rhinitis

Abstract: In spite of our recent insight into nasobronchial interaction mechanisms in allergic airway disease, the association between allergic rhinitis and voice complaints remains obscure. To evaluate the effects of nasal allergen provocation and seasonal grass pollen exposure on subjective and objective laryngeal parameters in singers with and without allergic rhinitis, an observational case control study was conducted. Prior to the pollen season, six grass pollen allergic and six non-allergic semiprofessional singer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a recent study on AR and laryngeal symptoms, involving six controls and six adult singers, nasal provocation with pollen extracts caused a rapid induction of laryngeal irritation and globus sensation. However, no objective changes occurred then, nor during the pollen season [90 ].…”
Section: Multi‐morbidities Of Allergic Rhinitismentioning
confidence: 99%
“…In a recent study on AR and laryngeal symptoms, involving six controls and six adult singers, nasal provocation with pollen extracts caused a rapid induction of laryngeal irritation and globus sensation. However, no objective changes occurred then, nor during the pollen season [90 ].…”
Section: Multi‐morbidities Of Allergic Rhinitismentioning
confidence: 99%
“…A previous clinical study with allergic singers reported the rapid induction of laryngeal complaints following allergen provocation and during pollen season. 1 In this study, a statistically significant increase in mast cell number and degranulation was detected in rat supraglottic laryngeal mucosal specimens upon allergen exposure. In addition, increased inflammatory cell infiltration in allergensensitized rat supraglottic laryngeal specimens was associated with inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 94%
“…However, the existing data regarding laryngeal mucosal response to allergy are limited and contradictory. A previous clinical study with allergic singers reported the rapid induction of laryngeal complaints following allergen provocation and during pollen season 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be interpreted in the following two different ways: the cause may arise from the disorder or from the medication intake. This is not surprising since allergic rhinitis is commonly associated with voice changes [37][38][39][40][41]. Singers tend to be in environments, such as stages, that are more prone to air, dust, or pollutants, which trigger these kinds of disorders [42][43][44].…”
Section: Discussionmentioning
confidence: 99%